In situ IR spectroscopic studies of the CO oxidation reaction over a ruthenium model catalyst - Farkas, Attila; Justus Liebig University Giessen (My University, 2008)
A complex ultrahigh vacuum (UHV) system for in situ IR spectroscopic studies of model catalysts was designed and built. The interface between the UHV system and the FTIR spectrometer is formed by an UHV reaction chamber with high-pressure capabilities, equipped with IR-transparent viewports. The setup allows the preparation and the in situ IR spectroscopic study of single-crystal model catalysts over an extended pressure range (10^-10 to ^-1 mbar) at temperatures in the 100-1200 K range. The model catalyst studied in the present thesis was an ultrathin RuO2(110) film epitaxially grown on the Ru(001) surface. The oxidation of CO on the model catalyst was studied by in situ reflection-absorption IR spectroscopy (RAIRS) in the spectral region of the C-O bond stretch vibrations (1800-2200 cm^-1). Our in situ RAIRS experiments at 350 K indicate that under stoichiometric and oxidizing conditions in the 10^-6 to 10^-3 mbar range, areas of the RuO2(110) surface are covered by clusters of densely packed CO molecules, characterized by IR absorption bands in the range 2060-2080 cm^-1. The RAIR spectra also indicate the existence of densely packed clusters of O atoms on the RuO2(110) surface. The oxidation of the aggregated CO molecules is very slow due to the high activation energies (1.2 eV) for CO and O diffusion on the RuO2(110) surface. We conclude that this practically inactive CO species is partly poisoning the catalyst surface. Further results include a RAIRS study of the process of reoxidation of a mildly reduced RuO2(110) surface and an in situ RAIRS study concerning the reduction of the RuO2(110) film to metallic ruthenium under intense exposure to CO.

Im Rahmen dieser Dissertation wurde eine komplexe Ultrahochvakuum-(UHV)-Anlage für die in situ IR-Spektroskopie an Modellkatalysatoren konzipiert, aufgebaut und in Betrieb genommen. Das Verbindungsglied zwischen UHV-System und FTIR Spektrometer bildet eine UHV-Reaktionskammer mit IR-optischen Fenstern, die auch für höhere Drücke einsetzbar ist. Dieser Aufbau erlaubt die Präparation und in situ IR-Spektroskopie an Modellkatalysatoren über einen weiten Druck (10^ -- 10^-1 mbar) und Temperaturbereich (100-1200 K). Bei dem hier untersuchten Modellkatalysator handelt es sich um einen dünnen RuO2(110)-Film, der epitaktisch auf Ru(001) aufgewachsen wurde. Die Kohlenmonoxid-Oxidation wurde auf diesem Modellsystem mittels in situ Reflektions-Absorptions-IR-Spektroskopie (RAIRS) in der C-O Streckschwingungsregion (1800-2200 cm^-1) untersucht. Die RAIRS Experimente bei 350 K zeigen, dass die Oberfläche sowohl unter stöchiometrischen als auch oxidierenden Bedingungen im Druckbereich von 10^-6 -- 10^-3 mbar mit Inseln von dicht gepacktem CO bedeckt ist, die durch IR-Banden im Bereich von 2060 bis 2080 cm-1 charakterisiert werden können. Außerdem beweisen die RAIR-Spektren die Existenz von dicht gepackten Sauerstoffinseln. Die Oxidation der CO-Inseln geht sehr langsam von statten, da die Aktivierungsenergie für die Diffusion von CO und O auf RuO2(110) mit cca. 1.2 eV vergleichsweise hoch ist. Es lässt sich schließen, dass diese praktisch inaktive CO-Phase den Katalysator zumindest partiell vergiftet. Weitere RAIRS-Untersuchungen in dieser Arbeit befassen sich mit der Reoxidation einer mild reduzierten RuO2(110)-Fläche und der Reduktion von RuO2(110) zu metallischem Ru(001) unter hohen CO-Dosen.
In situ IR-spektroskopische Untersuchung der CO Oxidation an einem Ruthenium-Modellkatalysator
Keywords: Oberflächenchemie; Schwingungsspektroskopie; Chemiesorption; Modellkatalyse; Ruthenium; model catalysis; spectroscopy; RAIRS IRAS; CO; ruthenium; ddc:540